2019
DOI: 10.1186/s41039-019-0114-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between interest and mathematics performance in a technology-enhanced learning context in Malaysia

Abstract: The primary aim of this preliminary study is to examine a possible association between interest and mathematics performance among Malaysian students in a technology-enhanced learning environment. The Mathematics Interest Inventory was administered to 40 students to measure students' interest towards mathematics, while a mathematics test was used to measure students' mathematics performance. Results of the descriptive statistical analyses revealed that the students were relatively interested in mathematics. Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
39
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 15 publications
11
39
2
2
Order By: Relevance
“…However, the findings of Yu and Singh (2018) showed a nonsignificant relationship between interest and mathematics performance. The finding of Wong and Wong (2019) could account for the inconsistent results of related findings. They found that interest is not significantly related to mathematics performance for high-achieving students, but interest has a significant, positive relationship with mathematics performance for low-achieving students.…”
Section: Introductionmentioning
confidence: 78%
“…However, the findings of Yu and Singh (2018) showed a nonsignificant relationship between interest and mathematics performance. The finding of Wong and Wong (2019) could account for the inconsistent results of related findings. They found that interest is not significantly related to mathematics performance for high-achieving students, but interest has a significant, positive relationship with mathematics performance for low-achieving students.…”
Section: Introductionmentioning
confidence: 78%
“…A preliminary study conducted by [46] on 150 students examining the association between the students' attitude and interest towards mathematics, students' perception on mathematic pedagogies and the subject itself, and their mathematics performance found that there is a moderately significant relationship between students' perception of mathematics and their mathematics performance. Article [47] also concluded that there is a significant relationship between interest and mathematics performance among Malaysian students who had lower mathematics performance, and igniting interest among low-performing students could lead to better performance. Study [48] revealed that the students' interest is one of the contributing factors in successful academic performance while [49] stated that interest in mathematics learning could be regarded as a predictor of mathematics achievement.…”
Section: Issues and Challenges In Mathematics Education In The Regionmentioning
confidence: 99%
“…A closer look at the elements of Stratum I of Carroll's (1993) theory will convince any observer that Africans are more likely to consider those indicators as irrelevant measures of nimdeε and nyansa. Given that interest affects practice and performance (Krapp et al, 1992;von Maurice et al, 2014;Wong and Wong, 2019), it is little wonder that Africans conceive intelligence in a way that is completely different form the current Western orthodoxy. Perhaps too, the construct of intelligence, as conceived in Western orthodoxy, is a specific form of what cognitive ability is while nimdeε and nyansa also may constitute a particular form of cognitive ability.…”
Section: Simple Reaction Taskmentioning
confidence: 99%